2008
DOI: 10.1111/j.1442-200x.2008.02702.x
|View full text |Cite
|
Sign up to set email alerts
|

Wheezing illness caused by respiratory syncytial virus and other agents

Abstract: Wheezing illness in infancy caused by RSV is more common in younger infants, but it is not more severe than that caused by other pathogenic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The most common diagnosis in hMPV‐infected children was pneumonia. The clinical manifestations of hMPV and RSV infections are very similar, and range from mild respiratory problems to bronchiolitis and pneumonia; consequently, they are difficult to distinguish clinically …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common diagnosis in hMPV‐infected children was pneumonia. The clinical manifestations of hMPV and RSV infections are very similar, and range from mild respiratory problems to bronchiolitis and pneumonia; consequently, they are difficult to distinguish clinically …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the incidence, clinical features, and genetic variability of hMPV . hMPV mainly causes bronchiolitis and pneumonia in infants . The peak of incidence of hMPV is mainly in the spring in temperate latitudes .…”
mentioning
confidence: 99%
“…In contrast, studies that compare individuals with RSV LRTI to those with LRTI due to other respiratory pathogens (e.g. human rhinovirus and bocavirus) usually find no difference in the risk of subsequent RWEC/asthma [28,30,[61][62][63][64][65][66][67][68][69][70][71][72][73], or find RSV LRTI to be inversely associated with these outcomes compared to the non-RSV LRTI exposed [74][75][76][77][78][79][80][81][82][83]. Several studies compared the same exposure group (with RSV LRTI medical events) to both types of comparison groups and found a positive association between RSV LRTI and RWEC/asthma when comparing exposed individuals to those without LRTI, but no significant association when compared to those with a non-RSV LRTI [36,41,52,53,75,76,[84][85][86][87][88].…”
Section: Observational Studiesmentioning
confidence: 99%
“…According to a birth cohort study, RSV was a risk factor for hospital admission with bronchiolitis. 5 However, its correlation to current wheezing remains uncertain at present. Respiratory viruses, such as human bocavirus (HBoV), human coronavirus (HCoV), and human metapneumovirus (hMPV), have been identified in children with lower RTIs, but its correlation to wheezing remains uncertain at present.…”
Section: Introductionmentioning
confidence: 99%